Comparison on the efficacy of dexpanthenol in sea water and saline in postoperative endoscopic sinus surgery - Fooanant S. (2014)
Objective: To compare the efficacy of dexpanthenol spray and saline irrigation in the postoperative care of sinusitis patients following endoscopic sinus surgery (ESS). Material and Method: One hundred twenty eight sinusitis patients undergoing ESS were randomly allocated to receive dexpanthenol spray (Mar plus) or saline irrigation twice a day for 4 weeks after the operation. Total nasal symptom score, crusting, infection, compliance, and patient satisfaction were evaluated at 1, 2-3, 4-6, and 12 weeks. Mucociliary clearance was assessed with the saccharin test before ESS and at the last visit. One hundred ten patients remained at the present study termination. Chi-square test and Mann-Whitney U test were employed. Results: Total nasal symptom score, mucociliary clearance, and infection improved in both groups after the operation. The dexpanthenol group resulted in a better mucociliary clearance than saline irrigation (9.93 ± 6.04 vs. 12.38 ± 9.32 min, p = 0.43). Saline irrigation resulted in a greater reduction of post nasal drip than dexpanthenol at the first visit (74% vs. 87%, p = 0.04). Compliance and patient satisfaction were comparable. Conclusion: The efficacy of dexpanthenol was comparable to nasal saline irrigation in the postoperative care of sinusitis patients following endoscopic sinus surgery. Dexpanthenol is an alternative treatment, which may be useful in young children and complicated cases.